Potential of Fish Scales in the Eco-friendly Treatment of Fish Processing Industry Effluent - Devasena, Subhashree; Padmavathy, P.; Manimekalai, D.; Jeya Shakila, R. (Fishery Technology, 2023)
The discharge of effluent from seafood processing units is loaded with several organic and inorganic contaminants. This results in the deterioration of water quality and leads to water pollution in water bodies where effluents are discharged. Huge quantities of fish scales are discarded as solid waste from fish markets. In the present study, fish scales were utilized as potential adsorbent and tested for their adsorption ability in the treatment of fish processing industry effluent. The prepared adsorbent caused a significant reduction (p50 %) in the concentration of alkalinity and hardness in the treated effluent. The concentration of Total solids (TS), Total Dissolved Solids (TDS), and Total Suspended Solids (TSS) showed significant (p